2015
DOI: 10.1039/c5tx00260e
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed proanthocyanidin extract protects against perfluorooctanoic acid-induced hepatotoxicity by attenuating inflammatory response, oxidative stress and apoptosis in mice

Abstract: Grape seed proanthocyanidin extract (GSPE) is a rich source of proanthocyanidins with multiple biological activities and potential health benefits. In the present study, we investigated the protective effect of GSPE against liver injury caused by perfluorooctanoic acid (PFOA) in mice and its possible mechanisms of action. Simultaneous treatment with GSPE for 14 consecutive days attenuated the functional and morphological changes in the liver of PFOA-exposed mice. Furthermore, simultaneous supplementation of GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Cleavage of caspase-3, a primary executioner of apoptosis, is the ultimate downstream event common to all three pathways (Kwak, 2013), and is therefore considered as a marker of cell apoptosis. In the present study, we showed that GSPE treatment significantly reduced the cleavage of caspase-3 induced by histones stimulation which is consistent with the anti-apoptotic effect of GSPE previously observed in the perfluorooctanoic acid-induced hepatotoxicity model (Liu et al, 2016). In addition, several other natural antioxidants, such as Bauhinia championii flavone, cyanidin-3-glucoside, and N -acetyl cysteine (NAC) have been previously reported to exert anti-apoptotic effects in cardiomyocytes (Jian et al, 2016), neurons (Ke et al, 2011), and human lymphocytes (Han et al, 2004), respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Cleavage of caspase-3, a primary executioner of apoptosis, is the ultimate downstream event common to all three pathways (Kwak, 2013), and is therefore considered as a marker of cell apoptosis. In the present study, we showed that GSPE treatment significantly reduced the cleavage of caspase-3 induced by histones stimulation which is consistent with the anti-apoptotic effect of GSPE previously observed in the perfluorooctanoic acid-induced hepatotoxicity model (Liu et al, 2016). In addition, several other natural antioxidants, such as Bauhinia championii flavone, cyanidin-3-glucoside, and N -acetyl cysteine (NAC) have been previously reported to exert anti-apoptotic effects in cardiomyocytes (Jian et al, 2016), neurons (Ke et al, 2011), and human lymphocytes (Han et al, 2004), respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have demonstrated that GSE can induce both apoptosis and cell cycle arrest, for example GSE increased G2/M phase arrest of the cell cycle leading to induction of apoptosis in a dose- and time-dependent manner in pancreatic cancer cell 28 . GSE also induces inhibition of cell growth in human bladder cancer cells by arresting cell cycle at G1 phase and inducing cell apoptosis 12 . In parallel, we observed that GSE treatment resulted in an increase in the expression of p53 and p21.…”
Section: Discussionmentioning
confidence: 99%
“…The consumer’s interest in GSE has been primarily due to its high content of antioxidants in the form of flavonoids, polyphenols and proanthocyanidins 10 , 11 . GSE has been shown to possess potent cardioprotective, hepatoprotective, antidiabetic, anti-mutagenic and anti-inflammatory properties 10 12 . Moreover, GSE has shown promising chemopreventive and anticancer effects in various cancer cells and in a wide variety of animal tumor models such as skin, colorectal, prostate and breast cancers 13 15 .…”
Section: Introductionmentioning
confidence: 99%
“…GSP protects cells from damage by controlling the oxidative damage by reducing the tissue injury and maintains antioxidant status and reduces the release of pro-inflammatory mediators (Aysun et al, 2008). Moreover, (Liu et al, 2016) showed that GSPE increased the expression of Nuclear factor erythroid 2-related factor 2 (NRF2) and its target antioxidant genes superoxide dismutase and catalase and decreased the production of malondialdehyde and hydrogen peroxide in the liver of mice exposed to perfluorooctanoic acid. A significant up-regulation of Bax, IL-1β and NF-κβ gene expression levels with significant down-regulation of Bcl-2 gene were observed in stomach of ethanol-induced gastric ulcerative rats.…”
Section: Discussionmentioning
confidence: 99%